Black seed oil ameliorated scopolamine-induced memory dysfunction and cortico-hippocampal neural alterations in male Wistar rats - A. Imam; M.S. Ajao; M.I. Ajibola; A. Amin; W.I. Abdulmajeed; A.Z. Lawal; A. Alli-Oluwafuyi; O.B. Akinola; A.O. Oyewopo; O.J. Olajide; M.Y. Adana (Bulletin of Faculty of Pharmacy Cairo University, 2016)
This study was conducted to evaluate cognitive enhancing effect and ameliorative effects of black seed oil in scopolamine induced rat model of cognitive impairment. These effects were investigated on scopolamine-induced dementia model in Morris water maze test (MWM) and Y maze test. The hippocampal histoarchitectural responses to scopolamine and Nigella sativa oil were also examined. Scopolamine (1 mg/kg ip) was given to induce dementia, followed by oral administration of BSO (1 ml/kg) for 14 consecutive days. MWM and Y-maze paradigms were used to assess hippocampal and frontal dependent memory respectively, thereafter the rats were sacrificed and brains were removed for histopathologic studies. Scopolamine resulted in memory impairment, by delayed latency in the MWM, reduced percentage alternation in the Y maze that was coupled by alterations in the cortico-hippocampal neurons. Posttreatment of rats with BSO mitigated scopolamine-induced amnesia, by reducing latency period and increasing percentage alternation and histological changes. The observed anti-amnestic effect of BSO makes it a promising anti-amnesic agent for clinical trials in patients with cognitive impairment.